Toward the Paperless Hospital? A Case Study of Document Use by Anaesthetists - Harper, Richard; O'Hara, Kenton; Sellen, Abigail; Duthie, D. (British Journal of Anaesthesia, 1997)
This report describes an ethnographic study of document use by anaesthetists. In doing so, it focuses on the role of the preoperative risk assessment form as used in anaesthetic practice at a cardiothoracic hospital, and considers what would be the advantages and disadvantages of shifting the paper into the electronic form. Evidence from this case study is used to comment on how the practical use of documents by medical professionals can be fundamentally at odds with how the organization at large would like to use them. We argue that hospital trusts need to take into account this practical perspective in order to build effective, on-line document systems.